Digitizing Documents on the Athabasca River Basin - Elliott, Colin (Athabasca River Basin Research Institute (ARBRI) Day, 2015)
The Repository expands upon ARBRI’s existing bibliography by providing accessibility to an extensive body of research and scholarly information relating to the Athabasca River Basin by digitizing materials, such as audio, video and text for online access. The Repository serves as a comprehensive open educational resource (OER) that contains accessible and interactive material for researchers, educators, students and other stakeholders.